KAJIAN EKSPERIMEN PENGGUNAAN SOLAR CELL SEBAGAI ALTERNATIF PENGISIAN AKUMULATOR 200Ah 12 Volt MESIN DIESEL PLTD - Yusuf, Bakharuddin; Darmanto, Seno; Handayani, Sri Utami; Susastro, Susastro (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2022)
PLTD (Diesel Engine Power Plant) is one generator used by several companies, especially electricity providers. It’s just that PLTD requires a large enough cost to produce electrical energy. Therefore it is necessary to make efforts to reduce operational costs, one of which is by making an alternative to charging the accumulator on the diesel engine. The alternatif is a prototype solar cell that can charge the 200 Ah 12 Volt accumulator so that the accumulator can be used for the starting process diesel engine (PLTD). So, at this writing the author tries to make an experimental study of the use of solar cells as an alternative to charging a 200 Ah 12 Volt accumulator which in this experimental study proceduces a 2 x 80 Wp mobile solar cell prototype that can be used for charging the accumulator of PLTD machines. In addition, from this experimental study, the results of accumulator charging of 1,444.92 Wh are sufficient to be used for the dynamo starter process on diesel diesel engines and the annual savings value is obtained.